Fabián Bielinsky´s Argentina: Reality and hiper-reality in times of crisis - Salas Murillo, Bértold (2018)
Argentina`s postrait at the beginning of XXI th century is analyzed by the producer and script writer Fabián Bielinsky in his movie pictures Nueve reinas (Nine queens) (2000) and El aura (2005). By using different narrative strategies, these movie pictures depict a violent and corruptive society. This article examines not only their characteristics of representation but also their narrative differences to think about different ways of “representing” reality.